Hubungan Durasi Pemberian Asi Dengan Status Gizi Anak Usia 0-24 Bulan di Puskesmas Simpang IV Sipin Kota Jambi Tahun 2015 - Amri, Nurul Khairiyah; Putra, Irawan Anasta; Karolina, Maria Estela (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2015)
ABSTRACT Background : The connection between breastfeeding duration starts on 0 Until 24 month and child's nutritional stat still bring some controversy. Positive and negative correlation can be seen ss result. This study purpose is to support the giving of exclusive breastfeeding for 2 whole years ( start from one hour after delivery, exclusive breastfeeding for 6 month, no bottle feeding, and 2 years or more of breastfeeding) in Jambi and the correlation with 0 – 24 month child’s nutritional state. Based on Jambi’s Health Departement data in 2013, there was counted 1545 exclusive breastfeeding on  0 – 6 months children  within 20  local Primary health care unit in Jambi. On Simpang IV Sipin area, there was 118 babies who got exclusive breastfeeding on 2013. Objective : To determine relationship between duration of  breastfeeding and nutritional status of children aged 0 – 24 months in Simpang IV Sipin Health Center Jambi in 2015. Methods : This Study used analytical research’s method with crosssectional approach held at Simpang IV Sipin Primary health care unit on 2015. This research used consecutive sampling to Primary health care unit the samples and got 73 children to be followed. This Study data been analyzed by using one- way Anova test. Results : Based on data, we can conclude that there is correlation between breastfeeding duration with nutritional state ( p value 0,037), child with normal nutritional state ( 29 children ) have breastfeeding duration for 8,9 month in average. Child with thin nutritional state have breastfeeding duration got 5,3 months in average, and child with fat nutritional state have breastfeeding duration got 10,2 month ib average. Conclusion: There is relationship between exclusive breastfeeding with nutritional status at age 0 – 24 months in Simpang IV Sipin Primary health care unit Jambi in 2015.   Keywords : Exclusive breastfeeding, nutritional status